Features vertebroneurological status in patients with nodular transformation of thyroid mation - N. N. Spirin; Yu. K. Alexandrov; Ye. L. Kasatkin; T. Yu. Nikanorova; A. N. Sencha (Бюллетень сибирской медицины, 2011)
Pathological processes in the thyroid and the cervical spine through the structures of the autonomic nervous system may provide each other mutual influence. Detection of additional pathogenetic factors in uzloobrazovaniya help develop additional methods of treatment and prevention tireopaty.